Chitinase producing Serratia marcescens for biocontrol of Spodoptera litura (Fab) and studies on its chitinolytic activities - Aggarwal, Chetana; Paul, Sangeeta; Tripathi, Vishwas; Paul, Bishwajeet; Khan, Md. Aslam (Annals of Agricultural Research, 2016)
In the present study different chitin-rich sources such as insect cadavers, prawn, fish scales were used for isolation of chitinolytic bacteria. Sixty four chitinolytic bacteria were isolated from these sources during 2011-2012. On the basis of zone of hydrolysis surrounding the bacterial colonies, twenty two isolates were selected for further studies. These were evaluated for their biocontrol potential against Spodoptura litura larvae. Insect mortality of the treated larvae ranged between 13.3 % to 70.8%. Serratia marcescens strain SEN caused highest mortality in the treated larvae and was selected for further studies. This strain was observed to possess good chitinase enzyme activity under alkaline conditions. pH optima for enzyme activity was observed to be pH 9. Even at pH more than 9, it was observed to possess higher enzyme activity than that observed at neutral or near neutral pH. As determined by in-gel activity, S. marcescens strain SEN was found to possess two isoforms with estimate molecular weight of ~51 kDa and 32 kDa. Thus, S. marcescens strain SEN is a good candidate as biocontrol agent for S. litura.Â